Trends in neurology medical education: a bibliometric analysis (2000–2023) - Fan, Yongxiang; Wang, Zijing; Zhang, Yuhao; Hu, Guangxin; Cao, Zhijie; Zeng, Guanda; Fu, Jiaming; Fu, Junyi (Frontiers in Education, 2025)
BackgroundThe development of neurology closely correlates with improvements in medical education, which provides essential knowledge and skills to tackle the growing global challenge of neurological disorders. This study aimed to perform a bibliometric analysis to assess the key areas and trends concerning the interface between neurology and medical education for the period spanning from 2000 to 2023.ObjectiveThis study aimed to perform a bibliometric analysis to assess the key areas and trends concerning the interface between neurology and medical education for the period spanning from 2000 to 2023.MethodsWe gathered articles from the Web of Science Core Collection database and employed two bibliometric tools, CiteSpace and VOSviewer, to evaluate and quantify various impact and collaboration metrics. Our analysis included annual publication data, journals, co-cited journals, countries/regions, institutions, authors, and co-cited authors. Furthermore, we identified emerging research areas linked to neurology and medical education by investigating the co-occurrence and bursts of keywords and co-cited references.ResultsFrom 2000 to 2023, a total of 900 articles investigating the correlation between neurology and medical education were published in 297 academic journals. These articles were authored by 4,399 researchers from 893 institutions across 92 countries/regions. The United States, England, and Canada emerged as the leading countries in this field, with the United States maintaining a dominant position. Harvard University was identified as the most productive institution. Gilbert Donald L emerged as the top author, while Jozefowicz Rf recorded the highest number of co-citations. The journal Neurology was not only the most prolific in publishing articles at the intersection of neurology and medical education but was also the journal that received the most co-citations. The main themes of these articles centered around psychology, education, social health, nursing, and medicine, with keywords frequently relating to education, students, and neurological disorders.ConclusionNeurophobia within neurology medical education remains a significant area of research, contributing to a deeper understanding of the relationship between neurology and medical training. Emerging areas such as resident education, medical education training, developmental neurology, and parental involvement may offer valuable guidance and new insights for further research in the field of neurology education.